Strengthening Community Businesses Through Creative Digital Promotion and Education - Alif Dewantara; Ahmad Herlyasa Sosro Pratama; Andik Pratama; Vierkury Metyopandi (Trescode Green Organization, 2024)
In 2020 - 2022, digital marketing practices will become increasingly prominent in response to the global COVID-19 pandemic, which has driven the transformation of society towards broader use of the digital realm. Apart from being a marketing tool, digital applications also play an essential role as a source of inspiration for individuals interested in starting an independent business. Within the framework of community service activities, the service team from Merdeka University Malang, together with students, carried out community service activities through the creative promotion of MSMEs and video tutorials that were beneficial to the community. This service activity involves the active participation of twenty students who are members of two different teams, namely the team responsible for its implementation.